An in-depth analysis of the personal factors and their pathways in shaping self-directed learning abilities among undergraduate nursing students - Li, Xiangxiang; Wang, Meifang; Feng, Xiujuan; Yin, Xiumin; Liang, Juan (Frontiers in Psychology, 2024)
Background Developing self-directed learning in undergraduate nursing students affects not only their learning and their lives, but also their future professional development and the quality of their future practice in clinical nursing. Hence, it is paramount to prioritize and cultivate self-directed learning capabilities among undergraduate nursing students, as this not only enhances their academic pursuits but also equips them with essential lifelong learning skills crucial for the dynamic healthcare landscape. Objective To delve into the intricate relationship between metacognitive abilities and self-directed learning practices among nursing students, while concurrently examining the mediating roles of psychological capital and interpersonal communication in this interconnected framework. This exploration aims to provide insights into how these factors interplay to influence the self-directed learning capabilities of nursing students. Methods A total of 662 undergraduate nursing students from one university in China were selected as participants in the survey, utilizing stratified random sampling between September 2023 and December 2023. Of these, an impressive 639 students (96.52%) provided valid responses. The Metacognitive Assessment Inventory, Adolescent Sense of Psychological Capital Scale, Supportive Communication Scale, and Self-Directed Learning Ability Scale were employed to comprehensively assess the metacognitive abilities, psychological capital, interpersonal communication skills, and self-directed learning capacities of nursing students. Pearson correlation analysis was subsequently utilized to delve into the related relationships among these variables. To test the mediating effects, the Bootstrap method, specifically Model 6 of the SPSS-Process package devised by Hayes, was applied. Results The findings revealed a robust positive correlation among metacognitive ability, psychological capital, interpersonal communication ability, and self-directed learning ability, with all associations reaching statistical significance at P < 0.01. Notably, the mediating roles of psychological capital and interpersonal communication in the relationship between metacognitive ability and self-directed learning were significant, as evidenced by the analysis (R2 = 0.347, F = 67.278, P < 0.001). Furthermore, the results indicated that metacognitive ability exerts an indirect influence on self-directed learning through a sequential chain of mediation involving psychological capital and interpersonal communication ability. Conclusions This finding highlights the intricate interplay between these factors, suggesting that enhancing nursing students' metacognitive abilities may indirectly bolster their self-directed learning by first fortifying their psychological capital and then fostering stronger interpersonal communication skills.